2009
DOI: 10.1089/jamp.2008.0693
|View full text |Cite
|
Sign up to set email alerts
|

A Gamma Scintigraphy Study to Investigate Lung Deposition and Clearance of Inhaled Amikacin-Loaded Liposomes in Healthy Male Volunteers

Abstract: Background:The purpose of this study was to investigate the inhalation of a liposomal formulation of amikacin in healthy male volunteers in terms of pulmonary deposition, clearance, and safety following nebulization with a commercial jet nebulizer. Methods: Amikacin was encapsulated in liposomes comprised of dipalmitoyl phosphatidylcholine (DPPC) and cholesterol via a proprietary manufacturing process (20 mg/mL final amikacin concentration). The liposomes were radiolabeled with 99m Tc using the tin chloride la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 24 publications
1
53
2
Order By: Relevance
“…[7][8][9][10][11][12][13] Targeted pulmonary delivery of antimicrobials (ie, antibacterials and antifungals) by inhalation aerosols is the subject of much recent interest in research and development, including several clinical trials. [8][9][10][11] Pulmonary liposomal aerosol delivery of antimicrobials can effectively fight infections, [14][15][16][17] and these liposomal delivery systems can be rendered into inhalable dry powder aerosols. 18 MOXI has been encapsulated in glutaraldehyde-crosslinked chitosan microspheres for intrapulmonary administration.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Targeted pulmonary delivery of antimicrobials (ie, antibacterials and antifungals) by inhalation aerosols is the subject of much recent interest in research and development, including several clinical trials. [8][9][10][11] Pulmonary liposomal aerosol delivery of antimicrobials can effectively fight infections, [14][15][16][17] and these liposomal delivery systems can be rendered into inhalable dry powder aerosols. 18 MOXI has been encapsulated in glutaraldehyde-crosslinked chitosan microspheres for intrapulmonary administration.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous effects, of NPs uptake and release, were demonstrated simultaneously, when a study of multilamellar liposomes containing rifampicin and isoniazid exhibited presence in alveolar macrophages and could maintain therapeutic concentrations in the lung tissue for 5 days [77]. Antimicrobial delivery via liposomes to the lungs has been shown to be beneficial in the case of cystic fibrosis and exhibits a controlled and sustained release, and some are currently in phase II clinical trials [78]. Studies involving the delivery of macromolecules such as siRNA have also been conducted using nanocarriers, as summarized more in depth elsewhere [73].…”
Section: General Approaches For Targeting Pulmonary Delivery Of Macromentioning
confidence: 99%
“…Liposomes also significantly (P<0.05) increased the fraction of drug delivered to the lower impinge stage and decreased the deposition in the upper stage of the impinger (Fig.3b). This suggests that nebulized liposomes may not only offer a sustained and localized drug effect in the respiratory airways (Taylor et al, 1989;Saari et al, 1999;Weers et al, 2009) but can also increase the dose delivered in "respirable" fraction. Thus, liposomes may play roles beyond entrapment of drugs when the Aeroneb Pro vibrating-mesh nebulizer is employed, with inclusion of lipid having a desirable effect on drug delivery and deposition in the "FPF".…”
Section: Nebulization Performance Studymentioning
confidence: 99%
“…Many studies have demonstrated that liposomes are generally safe for pulmonary delivery (Kellaway and Farr, 1990). Therapeutically, liposomes can prolong the action of the entrapped drug in the respiratory tract; hence they can potentially improve the therapeutic outcome and reduce the systemic adverse effects of the drug (Taylor et al, 1989;Saari et al, 1999;Weers et al, 2009). The main limitation of liposomes is their instability in aqueous dispersions, since phospholipids are liable to hydrolysis (Kensil and Dennis, 1981) and oxidation (Hunt and Tsang, 1981); this may cause the liposomes to aggregate or fuse, resulting in leakage of the drug originally entrapped.…”
Section: Introductionmentioning
confidence: 99%